Implementasi Convolutional Neural Network Untuk Klasifikasi Covid-19 - Asep Arwan Sulaeman; Andy Susilo (Teknik Informatika, Universitas Pelita Bangsa, 2022)
Covid-19 is a disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCo2). Covid-19 is a respiratory disease ranging from mild symptoms such as influenza to lungs such as pneumonia. Some scientists conducted research on Covid-19 by transferring knowledge to computers making this research more precise. One of them is the application of machine learning with deep learning methods. This can be done by building artificial intelligence using a simple Convolutional Neural Networks (CNN) algorithm to detect lungs x-ray exposed to Covid-19. The results of data testing can predict the image of the lungs that have been processed to obtain lung predictions in Covid-19 patients. The results show that the Convolutional Neural Network algorithm can produce an accuracy value of 95% for the Covid-19 prediction model with 50 epochs and 94% with 75 epochs. Keywords: Covid-19, machine learning, deep learning, convolutional neural network Algorithm.